Suicide from the perspective of Anthropology and Psychology: a look at Public Health (Research, Society and Development, 2023)
Introduction: suicide is an act voluntarily committed about an existing problem in man's life, there are several factors that help to contribute to this case, respectively, they can be family, social, economic and political issues, referred to as a set of actions that encompass and that is independent of sociocultural issues, ages, sexual preferences and gender identity. Objective: to understand suicide from the perspective of anthropology and psychology in a health perspective. Methodology: this work presents an experience developed in the field of Collective Health at a public university from the point of view of the Social, Human and Health Sciences, linked to the reflection of the academic community and the members of the course in the area of ​​health. Results and discussions: WHO began to classify suicide as a serious public health problem, suggesting the adoption of emergency public policies to prevent this problem in response to worrying epidemiological data, the statistical picture of suicide presents alarming numbers. Given the impact that this unlikely cause on Public Health, it was necessary for the state to intervene, adopting measures that work with surveillance/prevention with the creation of guidelines, financial incentives for the development of projects, in addition to establishing partnerships with support networks. Considerations: Involving health-oriented sectors is necessary because through them it is possible to develop strategies aimed at the promotion, prevention and rehabilitation of users and in this episode it is essential for them, as well as reducing this questioned problem as public health.